KOMBINASI KADAR KALIUM DAN SALINITAS MEDIA PADA PERFORMANCE JUVENIL UDANG GALAH (Macrobrachium rosenbergii de Man) - Mahendra Mahendra (Universitas Teuku Umar, 2015)
Purpose of this study is analyzing combination of potassium levels and the performance of juvenile prawns with media salinity. Experiment material is combination of potassium levels (25, 50, dan 75 ppm) and different media salinity (2, 4, dan 6 ppt). combination is obtained with 9 replication. Result of study show combination of potassium levels and media salinity giving effect to performance of juvenile prawns. Potassium levels with 75 ppm and media salinity 4 ppt have been given best performance to juvenile prawns (M. rosenbergii de Man).